Kajian Kebijakan Kesehatan dalam Upaya Pencegahan Hipertensi Masyarakat Pesisir Danau Tempe di Wilayah Kerja Puskesmas Liu - Khaeriah B; Ruslang Ruslang; Anugerah Yanuar Azis; Eka Wulansari; Tia Ailinnia (Lentera Pena Cendekia, 2025)
Hypertension is a major health issue contributing to cardiovascular complications in Indonesia, especially among the elderly. This study aims to evaluate health policies for hypertension prevention in the work area of Puskesmas Liu, specifically within the communities around Lake Tempe. The main focus of this research is to assess community understanding, the active role of Puskesmas, and the challenges faced in the implementation of hypertension prevention policies. The research method used is a qualitative phenomenological study with data analysis based on the Colaizzi approach. In-depth interviews were conducted with seven informants who are hypertension sufferers from the area during May-June 2025. The collected data were analyzed to identify key themes related to hypertension prevention policies. The results of the study show that the community’s understanding of hypertension and low-salt diets is still limited, with many people considering hypertension as an inherited condition. Puskesmas has conducted health education through Posbindu, but still faces challenges related to limited resources and educational media. The habit of consuming high-salt foods, particularly salted fish, poses a significant barrier to adopting a healthy diet. Family support also plays a crucial role in adherence to a healthy diet. This study emphasizes the importance of improving health education and involving families in hypertension prevention, as well as the need for more inclusive and community-based policies to effectively support hypertension prevention efforts.